2012
DOI: 10.1186/1479-5876-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cloned cells, animal model, and ATRA sensitivity of human testicular yolk sac tumor

Abstract: The testicular yolk sac tumor (TYST) is the most common neoplasm originated from germ cells differentiated abnormally, a major part of pediatric malignant testicular tumors. The present study aimed at developing and validating the in vitro and vivo models of TYST and evaluating the sensitivity of TYST to treatments, by cloning human TYST cells and investigating the histology, ultra-structure, growth kinetics and expression of specific proteins of cloned cells. We found biological characteristics of cloned TYST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Pediatric germ cell tumors account for 60–75% of pediatric testicular tumors, mostly as YSTs. The occurrence of the tumor in the cerebellar hemisphere is extremely rare and few cases have been reported in the literature ( 2 ). Endodermal sinus tumors, also known as YSTs, belong to an inferior class of germ cell tumors (GCTs) with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric germ cell tumors account for 60–75% of pediatric testicular tumors, mostly as YSTs. The occurrence of the tumor in the cerebellar hemisphere is extremely rare and few cases have been reported in the literature ( 2 ). Endodermal sinus tumors, also known as YSTs, belong to an inferior class of germ cell tumors (GCTs) with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a new generation drug named NVP-BEZ-235 that inhibits mTOR on proliferation, and apoptosis were reported previously because prior work suggested that NVP-BEZ-235 alone or the combination of NVP-BEZ-235 with another drug effectively slow down cancer cell proliferation [5]. Six human hepatocellular carcinoma cell lines including 97H, 97L, A3, F11, MHCC1 and SMMC7721, which recapitulate features of human liver cancers because these lines [6,7] were chosen to test the drug effects in the cell proliferation.…”
Section: N V P -B E Z -2 3 5 a N D S H B M 1 0 0 9 E F F E C T S O N mentioning
confidence: 85%
“…Six human hepatocellular carcinoma cell lines including 97H, 97L, A3, F11, MHCC-1, SMMC7721, and one gastric cell line, SGC-7901 cells, were purchased from the Cell Bank of Shanghai Institutes for Biological Science (CAS). TYST testicular cancer cell line was established by our group from the primary tissue of a patient [5]. They were cultured in Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% FBS (Biowest, France) and penicillin (100 U/mL)/streptomycin (100 mg/mL).…”
Section: Cell Culturementioning
confidence: 99%
“…Tumor antigens that can be recognized and attacked by host's adaptive immune responses are essential to effective antitumor immunotherapy. GPC3, as a carcinoembryonic antigen, is an ideal target for antitumor immunotherapy, because its expression is up‐regulated in many types of pediatric solid tumors, especially in YSTs 6,18 . Previous studies have shown that vaccination with GPC3 144‐152 peptide induces potent CD8 + T‐cell immunity against various types of cancers in rodents and in clinical trials 8,32 .…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that YST is the commonest GCT in preadolescent testicular tumors, and expresses high levels of GPC3 17 . Unfortunately, treatment of TYST still depends on surgical resection and/or chemotherapy 18 . Currently, there are few studies to explore the potential of GPC3 peptide‐based vaccines for treatment of TYST.…”
Section: Introductionmentioning
confidence: 99%